1990
DOI: 10.1055/s-0038-1634775
|View full text |Cite
|
Sign up to set email alerts
|

Expert Systems for the Prediction of Ovulation: Comparison of an Expert System Shell (Expertech Xi Plus) with a Program Written in a Traditional Language (BASIC)

Abstract: The use of an expert system shell (EXPERTECH Xi Plus) in the construction of an expert system for the diagnosis of infertility has been evaluated. A module was devised for predicting ovulation from the medical history alone. Two versions of this system were constructed, one using the expert system shell, and the other using QuickBASIC. The two systems have been compared with respect to: (1) ease of construction; (2) ease of knowledge base update; (3) help and explanation facilities; (4) diagnostic accuracy; (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
1994
1994

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…They report on the development of an expert system for the prediction of ovulation using an expert system shell and the programming language BASIC. Despite the general preconception that expert systems are best developed using expert system shells, Schreiner and Chard's study concluded that the construction of their system was not facilitated by the use of an expert system shell and that the BASIC version was superior in many respects [31]. While not a controlled study, this does illustrate some of the difficulties encountered when trying to use inappropriate tools to solve a clinical problem.…”
Section: A Preoccupation With Computer Artifactsmentioning
confidence: 95%
See 1 more Smart Citation
“…They report on the development of an expert system for the prediction of ovulation using an expert system shell and the programming language BASIC. Despite the general preconception that expert systems are best developed using expert system shells, Schreiner and Chard's study concluded that the construction of their system was not facilitated by the use of an expert system shell and that the BASIC version was superior in many respects [31]. While not a controlled study, this does illustrate some of the difficulties encountered when trying to use inappropriate tools to solve a clinical problem.…”
Section: A Preoccupation With Computer Artifactsmentioning
confidence: 95%
“…A study by Schreiner and Chard [31] illustrates the potential problems which may arise when the wrong tools are used. They report on the development of an expert system for the prediction of ovulation using an expert system shell and the programming language BASIC.…”
Section: A Preoccupation With Computer Artifactsmentioning
confidence: 99%